Recent Advances in Bunyavirus Reverse Genetics Research: Systems Development, Applications, and Future Perspectives - Ren, Fuli; Shen, Shu; Wang, Qiongya; Wei, Gang; Huang, Chaolin; Wang, Hualin; Ning, Yun-Jia; Zhang, Ding-Yu; Deng, Fei (Frontiers in Microbiology, 2021)
Bunyaviruses are members of the Bunyavirales order, which is the largest group of RNA viruses, comprising 12 families, including a large group of emerging and re-emerging viruses. These viruses can infect a wide variety of species worldwide, such as arthropods, protozoans, plants, animals, and humans, and pose substantial threats to the public. In view of the fact that a better understanding of the life-cycle of a high pathogenic pathogen is often a precondition for developing vaccines and antivirals, it is urgent to develop powerful tools to unravel the molecular basis of the pathogenesis. However, biosafety level (BSL)-2, -3, or even -4 containment laboratory is considered as a necessary condition for working with a number of bunyaviruses, which has hampered various studies. Reverse genetics systems, including minigenome (MG), infectious virus-like particle (iVLP), and infectious full-length clone (IFLC) systems, are capable of recapitulating some or all steps of the viral replication cycle; among these, the MG and iVLP systems have been very convenient and effective tools, allowing researchers to manipulate the genome segments of pathogenic viruses in a lower BSL or outside biocontainment facilities to investigate the viral genome transcription, replication, virus entry, and budding. The IFLC system is generally developed based on the MG or iVLP systems, which have facilitated the generation of wild-type or recombinant infectious viruses. These established reverse genetics systems have been employed as powerful tools for researchers to understand bunyavirus biology, identify important virulence factors, and develop antiviral drugs and vaccines. The MG, iVLP, and IFLC systems have been successfully developed for some important bunyaviruses and have been widely used to investigate the viral replication cycle, virus–host interactions, virus pathogenesis, and evolutionary process. The majority of bunyaviruses are generally enveloped negative-strand RNA viruses with two to six genome segments, of which the viruses with bipartite and triplicate genome segments have mostly been characterized. This review aimed to summarize current knowledge on reverse genetic studies of representative bunyaviruses causing severe diseases in humans and animals, which will contribute to the better understanding of the bunyavirus replication cycle and provide some hints for developing designed antivirals.